2008
DOI: 10.1002/huon.200800008
|View full text |Cite
|
Sign up to set email alerts
|

Maternal deprivation and overnutrition in early postnatal life and their primary prevention: Historical reminiscence of an “ecologic experiment” in Germany

Abstract: During critical developmental periods in early life, altered environmental conditions can lead to pre-and early postnatally acquired, life-long malfunctions and subsequent diseases (Perinatal Programming). Avoiding unfavourable conditions during early development may thus open possibilities of primary prevention.At the beginning of the 21 st century, demographic aging and increasing overweight prevalences are two major problems nearly world-wide. Interestingly, during the second half of the last century, an ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…have adopted an important measure for early-life prevention of NCDs. As a successful example, the intense promotion of breastfeeding initiated by East Germany yielded a lower prevalence of obesity in young individuals compared to that in the corresponding West Berlin population, which was not introduced to intense breastfeeding (Dörner, Rodekamp, & Plagemann, 2008).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…have adopted an important measure for early-life prevention of NCDs. As a successful example, the intense promotion of breastfeeding initiated by East Germany yielded a lower prevalence of obesity in young individuals compared to that in the corresponding West Berlin population, which was not introduced to intense breastfeeding (Dörner, Rodekamp, & Plagemann, 2008).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Conceptually, Dörner also contributed by introducing the term 'programming' (die Programmierung) in the sense that it is now, rightly or wrongly, used and he argued for the notion of 'functional teratogenesis' to describe the observed phenomena. 24,26 Along the same lines and at the same time, the diabetologist Norbert Freinkel developed the hypothesis of 'fuel-mediated teratogenesis' to explain how the metabolic state of the mother could influence her offspring as well as intergenerational transmission of risk of diabetes. In his 1980 Banting lecture, he stated that 'developing fetal structures may be exquisitely attuned to fine alterations in maternal fuel economyy It is suggested that concepts of teratogenesis should be expanded to include alterations occurring subsequent to organogenesis during the differentiation and proliferation of fetal cells.…”
Section: The Emergence Of the Dohad Conceptmentioning
confidence: 99%
“…Although research on the relation between early weight gain and later overweight risk has only recently achieved broad attention, fi rst studies on this subject date back to the 1970s. Already in 1977, D ö rner et al reported that excessive weight gain during the fi rst months of life was a decisive risk factor for later overweight ( [7,9,10] ; for review see [8] ). During recent years, the body of data showing that increased early weight gain is an independent risk factor for later overweight has been increasing continuously.…”
Section: Discussionmentioning
confidence: 99%